Efficiently reduce working hours in SMEs and large companies in Ecatepec. - González Hernández, José de Jesús; Fierro Rosales, Laura; Vázquez Ibarra, Irene; López Espinosa, Irma (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2026)
OBJECTIVE: To analyze the current reform to the Federal Labor Law in Mexico regarding reducing the working day for workers in SMEs, generating greater impact and shared benefits in companies in the municipality of Ecatepec.MATERIAL AND METHOD: The study was conducted using a 10-question questionnaire administered by telephone. It was an exploratory quantitative study, employing an analytical approach. A total of 147 questionnaires were administered in SMEs, were considered 235 companies distributed as follows: 30 in micro-enterprises, 40 in small, 43 in medium and 34 in large companies.RESULTS: In 83% of the companies agree that improving their processes to accommodate reduced working hours is necessary. In 93% of the companies agree that less stress will lead to a reduction in accidents and illnesses. In 100% of the companies believe that reducing working hours will foster a stronger sense of belonging among employees.CONCLUSIONS: Reducing the working hour-day can be done in a planned way, without causing a business setback or problem; they will only have to train and improve their working methods, thus allowing them to be more productive.
Keywords: law; work; working day; companies; schedules.